How Indians responded to the Arogya Setu app? - Prakash Babu Kodali; Sibasis Hense; Swarajya Kopparty; Gangadhar Rao Kalapala; Banashri Haloi (Wolters Kluwer Medknow Publications, 2020)
The mHealth app Arogya Setu can substantially contribute to the containment and management of COVID-19. This study explores the experiences and expectations of Arogya Setu app users by conducting a combined content analysis of their reviews. Five hundred and three most relevant reviews were analyzed using the descriptive statistics and thematic analysis. The reviews are primarily posted in the areas of user acceptance (80%), app usefulness (72.8%), and app features (62.2%). The thematic analysis resulted in four themes: user acceptance, app usefulness, promptness of the Indian Government in bringing the app on time, and concerns and cautions raised by the users. These help in strengthening the app features enabling the real-time data capture and analytics and providing timely information to authorities for better decision-making.